PERSEPSI HARGA, CITRA MEREK, PERLUASAN MEREK, POSITIONING DAN DIFERENSIASI PRODUK TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA AIR MINERAL MEREK AQUA (Students' Journal of Economic and Management, 2015)
This study wants to examine the factors that influence the purchasing decisions of customers bottled mineral water. Factors that were tested in this study is the price, brand image, brand extension, positioning, differentiation as an independent variable while purchasing decisions as the dependent variable. The study sample consisted of 100 respondents who consume bottled mineral water in Terminal Terboyo Semarang. The data used in this study are primary data and sample selection using accidental sampling method. The analysis tool used is multiple regression analysis at a significance level of 5%. Hypothesis testing results show that the price of products Aqua no significant negative effect on consumer purchasing decisions. Brand image Aqua significant positive effect on consumer purchasing decisions. Brand extension is not insignificant positive effect on consumer purchasing decisions. Positioning is not insignificant positive effect on consumer purchasing decisions. Differentiation significant positive effect on consumer purchasing decisions. Keywords: price, brand image, brand extension, positioning, differentiation and purchasing decisions